2020
DOI: 10.1007/s11368-020-02727-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of water retention functions of artificial soil-like substrates for a range of mixing ratios of two components

Abstract: Purpose Urban greening is politically fostered as an adaptation strategy to climate change. Therefore, the demand for fertile planting substrates increases. Such substrates are usually mixed from mined geogenic resources but should rather be produced from recycled materials. Furthermore, their hydraulic properties should be designed according to their application, e.g., by optimizing the mixing ratio of their components. Therefore, this study introduces an approach to investigate the water retention curves (WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 36 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…Other parameters for soil structural performance (e.g., infiltration rate, pore volume, water-holding capacity) will be essential for the applicability and application decisions of engineered soil alternatives. Future research should address the water-retention curves additional to the grading curves, to assure the long-term functionality of the optimized soil alternatives for applications in sustainable rainwater management [69].…”
Section: Geotechnical Accordance and Soil Structural Stability Perfor...mentioning
confidence: 99%
“…Other parameters for soil structural performance (e.g., infiltration rate, pore volume, water-holding capacity) will be essential for the applicability and application decisions of engineered soil alternatives. Future research should address the water-retention curves additional to the grading curves, to assure the long-term functionality of the optimized soil alternatives for applications in sustainable rainwater management [69].…”
Section: Geotechnical Accordance and Soil Structural Stability Perfor...mentioning
confidence: 99%
“…The function of the BC relies on the performance of the biofilter soil layer which is formed, in many cases, by specifically designed constructed soil (Gulbaz and Kazezyilmaz-Alhan, 2017;Hatt et al, 2009) mostly composed of sand, various types of topsoil and organic material. The ratio of these components affects the resulting retention properties (Willaredt and Nehls, 2021) hydraulic conductivity of the mixture, which predetermines the infiltration rate in the bioretention cell and the overall functioning of the biofilter layer (Zhang and Chui, 2017). Gulbaz and Kazezyilmaz-Alhan (2017) showed that a high sand ratio decreases the arrival time of a peak flow bioretention system and increases the outflow peak whereas high clay and silt contents increase the arrival time and decrease the peak of the outflow of the bioretention system.…”
Section: Introductionmentioning
confidence: 99%
“…These constructed Technosols can be engineered from locally available valuable mineral and organic waste. This is considered a sustainable path to meet the demand (Prado et al, 2020;Deeb et al, 2020;Fabbri et al, 2021), as it reuses materials that would otherwise be land filled and decreases the degradation of fertile natural soil resources and other geogenic materials (Willaredt and Nehls, 2021). Tams et al (2022) showed in a life cycle analysis, that the use of recycled brick particles instead of expanded clay reduces the CO2 footprint of the substrate layer by 50 % in an extensive green roof.…”
Section: Introductionmentioning
confidence: 99%
“…Tams et al (2022) showed in a life cycle analysis, that the use of recycled brick particles instead of expanded clay reduces the CO2 footprint of the substrate layer by 50 % in an extensive green roof. The composition of waste materials and the processing (Ulrich et al, 2021) are the most important design levers to manipulate the properties according to their targeted application (Rokia et al, 2014;Fields et al, 2018;Willaredt and Nehls, 2021). Most UGI addresses the re-establishment of soil function related to the regulation of the water cycle (Grabowski et al, 2022).…”
Section: Introductionmentioning
confidence: 99%